Sanksi Pidana Bagi Dosen Sebagai Pelaku Tindak Pidana Pelecehan Seksual Kepada Mahasiswa - Ni Komang Arik Darmayanti; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2022)
Harassment comes from the word harass which means to look down on, insult, or be worthless. While the word sexual comes from the word sex, very often interpreted as biological sex, namely male and female. So sexual harassment has the meaning of degrading, or insulting men or women. Sanctions are a result of criminal acts committed by people who violate the law. This research was conducted to determine the sanctions and penalties that can be imposed on perpetrators of sexual harassment by lecturers against students. By using the normative legal method which is closely related to legal facts and existing laws and regulations, the technique is also carried out with an inventory in the collection of research legal materials. Utilize primary, secondary and tertiary sources that will be used in analyzing data. The results obtained after the research are legal arrangements for perpetrators of sexual harassment crimes can be charged with obscenity articles (Articles 289 to 296 except Article 291 of the Criminal Code). This crime of sexual harassment was committed by a lecturer and was subject to criminal sanctions from the Judge's Decision which could be snared with a sentence of 7 months.